Antimicrobial resistance: Attitudes, knowledge and practices in society - International Livestock Research Institute (International Livestock Research Institute, 2021)
Seventy per cent of Uganda’s population is employed in the agricultural sector, with the majority keeping some form of poultry. This video documents the use of antibiotics in the Uganda poultry industry as well as the knowledge, attitudes and practices around antimicrobial resistance (AMR) among different value chain actors.